KONDISI FISIK LINGKUNGAN PERMUKIMAN YANG TUMBUH TIDAK SESUAI PERUNTUKAN LAHAN DAN KONSEP YANG TERBENTUK DARI ABSTRAKSI KONDISI PERMUKIMAN DI PUNGGUNG BUKIT KELURAHAN KELAPA LIMA KOTA KUPANG - Ndolu, Chrisjany; Effendi, Jauhari; Ramang, Ruslan (Bumi Lestari, 2017)
The purpose of this study to determine the condition of human settlements on the ridges do not develop according to their appropriation and formulate concepts as abstraction of a describe the condition settlements on the ridge.This study used a qualitative approach to the way of thinking that is inductive to a specific method of analysis of data from the field into units of analysis and continued with categorization. Researchers act as the main instrument to collect data withinterviews and observation in the study site.To ensure the validity of the data examined by triangulation techniques. The results showed that the units of neighborhoods that grow not suitable land use along the ridge at the Kelapa LimaVillage, District of Kelapa Lima, Kupang, has formed a concept consisting of the physical building and physical infrastructure. Physical building appear from (1) Concept Occupancy Irregular pattern, (2) The concept of Rule of Law. Physical infrastructure appears from (1) Concept Insufficient Environmental Facility, (2) community and social participation.